A case study about the comprehension of electromagnetic induction in Northern Italy. (August 2019) - Giliberti, M; Giliberti, E; Cavinato, M
Abstract: We discuss a study about Italian upper secondary school, undergraduate and graduate students' and teacher's misunderstanding in dealing with electromagnetic induction. We suspect that most difficulties, that we found substantially common at all levels of education, come from the very poor link, generally presented in teaching, between the Faraday's law and the Lorentz force. We also suggest that the understanding of inductive phenomena/problems/exercises could benefit from taking into account also the magnetic vector potential "point of view".